Investigation of anticancer effects of Meteorin like protein on different human cancer cell lines (Annals of Medical Research, 2024)
Aim: Cancer is one of the biggest health problems threatening humanity, and the fight against cancer continues with different methods worldwide. Despite advances in cancer prevention and treatment, the low success rate and tumor recurrence make the discovery of new alternative agents important. Adipokines are among those known to be associated with cancer. The relationship of the peptide-structured Meteorin like protein (Metrnl), a member of the adipokine family, discovered in 2012, with cancer remains a mystery. This study was conducted to examine the cytotoxic effects of Metrnl on human ovarian, prostate, colon and breast cancer cell lines.Materials and Methods: In the study, ovarian (A2780), human prostate (LNCaP), colon (Caco-2) and breast cancer (MCF-7) cell lines were used. After the cells were incubated with 1, 5, 10, 50, 100 and 200 ng/mL Metrnl for 24 h, the cytotoxicity level was determined by the 3-(4,5-dimethylthiazol-2-yl)-2,5diphenyltetrazolium bromide (MTT) assay method. determined. Comparisons between groups were made with the Kruskal Wallis H-Test.Results: Concentrations of Metrnl significantly reduced cell viability in A2780, LNCaP, Caco-2 and MCF-7 cell lines (p
Keywords: Meteorin like protein; Cytotoxicity; Ovarian cancer; Prostate cancer; Colon cancer; Breast cancer